Implemetasi Metode Seamless Learning dalam Pembelajaran Aqidah Akhlak untuk Meningkatkan Kemandirian Siswa di Madrasah Ibtidaiyah Salafaiyah Prambontergayang - Ahmad, Ainur Rizqi (Madrasah Ibtidaiyah Education Journal, 2025)
Along with the development of technology and the demands of 21st-century education, innovative learning methods are needed to improve the quality of education, including learning aqidah and akhlak. One method that can be implemented is the Seamless Learning method, which integrates formal and informal learning. This study aims to explore how the Seamless Learning method can be applied in learning aqidah akhlak to increase student independence. Through this approach, it is expected that students will not only understand the concept of aqidah akhlak but also be able to apply it in everyday life. This research uses qualitative methods with data collection through observation, interviews, and literature studies. The application of the seamless learning method at Madrasaha Ibtidaiyah Salafiyah Prambontergayang is one method that encourages students to carry out learning independently, with learning that can be carried out in class and outside the classroom, and can use information technology in the form of cellphones to access knowledge and information on learning aqidah akhlak, accompanied by parents. The results showed that the application of the Seamless Learning method can increase students' independence in learning aqidah akhlak, and encourage them to be more active in exploring moral values in their environment.